KARAKTERISTIK ALTERASI DAN MINERALISASI CEBAKAN TEMBAGA DI DAERAH SETELUK DAN SEKITARNYA, KABUPATEN SUMBAWA BARAT, PROVINSI NUSA TENGGARA BARAT: THE CHARACTERISTIC OF ALTERATION AND MINERALIZATION OF COPPER DEPOSITS IN SETELUK AREA AND ITS SURROUNDING, WEST SUMBAWA DISTRICT, WEST NUSA TENGGARA PROVINCE - Widi, Bambang Nugroho; Edya Putra (Pusat Sumber Daya Mineral Batubara dan Panas Bumi, 2021)
The research was conducted by the background of gold mining community around the research area. The purpose of the study was to know the continuity and type of mineralization that had been previously found outside the study area. The methods used include geological mapping and geochemical sampling of river sediments, rocks and pan concentrates. Laboratory analysis carried out at PSDMBP includes chemical analysis of the AAS method, petrographic examination, mineragraphy, grain mineralogy and Spec-Terra. Mineralization in the Seteluk area and its surroundings is one of the most interesting forms of mineralization occurring in intrusive granodiorite, volcanic and sedimentary rocks. There are three forms of indication of mineralization, namely; Firstly is low sulfidation epithermal mineralization, characterized by the presence of quartz veins breaking through the argillic zone (illite, montmorillonite, and kaolinite) in the sandstone with mineral associations of chalcopyrite, sphalerite, galena and pyrite. Both high sulfidation epithermal mineralizations are characterized by the presence of massive silica in which there is a localized vuggy silica structure of sulfur with alteration minerals of pyrophyllite, jarosite, and pyrite sulfide. The three porphyry indications are thought to occur in granodiorite with the main characteristics of epidote alteration, chlorite with veinlets and magnetite spots. The identified metallic minerals have associations of magnetite, ilmenite, chalcopyrite, galena, sphalerite, covelite and iron oxide. The results of rock chemistry analysis showed the highest Au content was 98 ppb; Cu 774 ppm, Pb 7993 ppm and Zn 23007 ppm. Indications of Au and Cu mineralization are also known from panning results in the form of gold and chalcopyrite grains with the percentage of chalcopyrite grains reaching 53%. The alteration and mineralization pattern shows the appearance of magnetite with ilmenite, chalcopyrite and pyrite in the granodiorite intrusion which is estimated to be a potassic zone (?) then towards the outside of the silica zone, advanced argillic, argillic zone and the outermost propylite zone. This area is thought to be a porphyry (?) type mineralization system in the interior, followed by high sulfidation and then low sulfidation epithermal mineralization with mineralization centers estimated to be below the surface.